The role of psychosocial factors in mediating the treatment response of epidural steroid injections for low back pain with or without lumbosacral radiculopathy: A scoping review. - Meredith Stensland; Donald McGeary; Caleigh Covell; Elizabeth Fitzgerald; Mahsa Mojallal; Selena Lugosi; Luke Lehman; Zachary McCormick; Paul Nabity (PLoS ONE)
Epidural steroid injections (ESIs) are often used to treat low back pain (LBP) due to lumbosacral radiculopathy as well as LBP without a clear component of radiculopathy, in some cases. While it is increasingly recognized that psychosocial factors are associated with pain outcomes, few studies have assessed the contribution of these factors to common pain interventions like ESIs. This study aimed to summarize the scope and nature of how psychosocial factors are accounted for in research on ESIs for the treatment of LBP with or without lumbosacral radiculopathy and to identify gaps and recommendations for future research. A scoping review following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis-Scoping Review Extension framework was conducted. Publications dated before September 2023 were searched in PubMed, CINAHL, Scopus, PsycINFO, and Google Scholar. Of the 544 records identified through database searching, a total of 51 studies cumulatively totaling 10,447 participants were included. Sample sizes ranged from 12 to 5,104 participants. Of the 51 included studies, only 10 (20%) analyzed and reported the relationship between at least one psychosocial variable and post-injection pain at any follow-up timepoint. The other 41 (80%) included no analyses examining ESI response as a function of psychosocial variables. Based on the studies that included analysis by psychosocial variables, poor psychosocial functioning appears to be associated with inferior treatments outcomes following ESI for back pain with or without lumbosacral radiculopathy. Relative to the vast body of literature on ESIs for LBP and lumbosacral radiculopathy, minimal attention has been directed to the influence of psychosocial factors on ESI treatment outcomes. Future research evaluating predictors of the effect of ESI on pain relief should include development of more comprehensive models containing modifiable psychosocial variables as predictors of ESI response.